Uwagi o strukturze i przekładzie skrótowców z dziedziny wojskowości i przemysłu w Słowniku rosyjsko-polskim Józefa Krasnego - Sobczak, Michał (Acta Polono-Ruthenica, 2019)
This paper examines the structure and translation of industry and military abbreviations compiled by Józef Krasny in the Moscow Russian-Polish dictionary. The first section refers to abbreviations as language units and focusing on the interwar period, provides a brief historical context of abbreviations in the Russian language. It further describes terminological and classification problems and refers to selected aspects of translation.The paper aims first and foremost to analyse the structure of the extracted initialisms, syllabic and complex abbreviations and clipped forms. In addition, it deals with models of their translation and lexicographic representation. Ultimately, it evaluates if the choice of Polish equivalents for Russian abbreviations in the dictionary in question is adequate and consistent.